COVID-19 Pulmonary and Olfactory Dysfunctions: Is the Chemokine CXCL10 the Common Denominator?. (June 2021) - Oliviero, Antonio; de Castro, Fernando; Coperchini, Francesca; Chiovato, Luca; Rotondi, Mario
COVID-19 is an ongoing viral pandemic that emerged from East Asia and quickly spread to the rest of the world. SARS-CoV-2 is the virus causing COVID-19. Acute respiratory distress syndrome (ARDS) is definitely one of the main clinically relevant consequences in patients with COVID-19. Starting from the earliest reports of the COVID-19 pandemic, two peculiar neurological manifestations (namely, hyposmia/anosmia and dysgeusia) were reported in a relevant proportion of patients infected by SARS-CoV-2. At present, the physiopathologic mechanisms accounting for the onset of these symptoms are not yet clarified. CXCL10 is a pro-inflammatory chemokine with a well-established role in the COVID-19-related cytokine storm and in subsequent development of ARDS. CXCL10 is also known to be involved in coronavirus-induced demyelination. On these bases, a role for CXCL10 as the common denominator between pulmonary and olfactory dysfunctions could be envisaged. The aim of the present report will be to hypothesize a role for CXCL10 in COVID-19 olfactory dysfunctions. Previous evidences supporting our hypothesis, with special emphasis to the role of CXCL10 in coronavirus-induced demyelination, the anatomical and physiological peculiarity of the olfactory system, and the available data supporting their link during COVID-19 infections, will be overviewed.